AIAA SCITECH 2022 Forum 2022
DOI: 10.2514/6.2022-1551
|View full text |Cite
|
Sign up to set email alerts
|

Aeroelastic Wing Demonstrator with a Distributed and Decentralized Control Architecture

Abstract: This study investigated the design and development of an autonomous aeroservoelastic wing concept with distributed flaps. This wing demonstrator was developed in the scope of the SmartX project, aiming to demonstrate in-flight performance optimization and multi-objective control with over-actuated wing designs. Following a successful test campaign with a previous wing design based on active morphing, this study aims to develop an over-actuated aeroelastic wing design suitable for aeroelastic control, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In a previous study, the effect of damping and stiffness variation of the actuator dynamics of the aeroservoelastic model were studied [19]. The study demonstrated that as the bandwidth of the actuator is increased (π‘˜ < 1), the controller was able to react more effectively to the gust disturbance and exhibited better performance.…”
Section: Impact Of Actuator Damping and Stiffness Combined With Uncer...mentioning
confidence: 98%
See 2 more Smart Citations
“…In a previous study, the effect of damping and stiffness variation of the actuator dynamics of the aeroservoelastic model were studied [19]. The study demonstrated that as the bandwidth of the actuator is increased (π‘˜ < 1), the controller was able to react more effectively to the gust disturbance and exhibited better performance.…”
Section: Impact Of Actuator Damping and Stiffness Combined With Uncer...mentioning
confidence: 98%
“…The quadratic relationship in Eq. ( 9) ensures that the natural frequency of the actuator dynamics is scaled proportionally, while the damping ratio is kept invariant [19]. It is not trivial to fully characterize actuator uncertainties in complex systems, however, a widely adopted first-order approach in the aeroelasticity domain is a free-play model which described a dead-band between commanded and actual actuator input [20]:…”
Section: Actuator Dynamics and Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation